"Are your employees mentally prepared for the pandemic?" Wellbeing-oriented human resource management practices in a developing country. (February 2023) - Ngo, Tramy; Le, Dung; Doan, Tin
Abstract: Employees are the most valuable asset of any service business because of its human-centric nature. However, in the crisis situations, the human side in crisis management strategy, particularly in the areas of human resource management is largely overlooked. The present study explores how human resource management (HRM) practices in the pre-crisis stage could build a good foundation of psychological capital (PsyCap) for tourism and hospitality staff to be mentally resilient during the COVID-19 pandemic. Grounded on the conservation of resource (COR) theory, research hypotheses are developed and then empirically tested using a sample of 760 employees in various tourism and hospitality companies. Research outcomes demonstrate that wellbeing-oriented HRM policies (specifically employee development and employee empowerment policies) in the pre-crisis stage increases employee PsyCap during the pandemic, leading to the preservation of their wellbeing. More importantly, employees' family financial burden is found as a moderating factor, altering the influences of HRM policies on employee PsyCap and their in-crisis wellbeing. Therefore, wellbeing-oriented HRM could be part of crisis preparedness strategy for tourism and hospitality businesses as well as crucial element of the internal corporate social responsibility portfolio in tourism and hospitality businesses. In developing countries, where less financial support and fewer job security policies are available during crises than in the developed world, the application of wellbeing-oriented HRM becomes even more critical. Highlights: Addressing the research gap on the human side of business crisis management. Building employees' psychological capital (PsyCap) is essential in crisis management. Employees with dependents in a developing country is more impacted by the pandemic. Recommending employee well-being oriented human resource management.